La signoria rurale nell'Italia del tardo medioevo. 2 Archivi e poteri feudali nel Mezzogiorno (secoli XIV-XVI) - Salvestrini, Francesco; SENATORE, Francesco (Reti Medievali E-Book, 2021)
By studying the archives of the feudal Lords of Southern Italian between the 14th-16th centuries you can understand the real nature of their power and how it was expressed. The volume, which takes into account the most recent historiography, relies on the study and inventory of important documentary collections held in the Archivio di Stato of Naples, such as the Sommaria (Relevi with the files for feudal succession; Dipendenze, I, Conti erariali dei feudi and Diversi, with the seigneurial account books acquired by the State of those lord who had been rebellious or had died without heirs). The authors deal also with the cartularies ('platee') of aristocratic dynasties as the Ruffo and the Sanseverino, based in Calabria, and with the parchments of the Albertini from Nola. Thanks to the rich information derived by these archival series and account books, the authors bring new light on the seigneurial powers, the typology of the records produced by and for the Lords, the administration of their estates, the strategy for elaborating the family memory.